Georgia : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that Georgia's real GDP growth averaged 6 1\2 percent in 2011-2012, about 1 1\2 percentage points more than projected at the 2011 Article IV consultation. Inflation has declined steadily, reflecting lower food prices, lagged effects of exchange rate appreciation, and cuts in administered energy prices. The exchange rate has faced appreciation pressures, but has been kept stable against the U.S. dollar. However, the economy has slowed down markedly since mid-2012, and unemployment remains high at 15 percent. Despite the slowdown, growth could still reach 4 percent in 2013, rising to about 6 percent in 2014 and beyond.